Analytical Behaviour of Biacetyl Monoxime Thiosemicarbazone Towards Ni(II), Cu(II) and Pd(II) Metals - Kumar Dwivedi, Prabhat; Kumar Das, Anil; Mishra, P.M. (Asian Journal of Chemistry, 2010)
Complexes of Ni(ll), Cu(ll) and Pd(ll) have been synthesized with biacetyl monoxime thiosemicarbazone and structures of the complexes have been determined and found to be ML2. This new reagent can be used over a large concentration range for gravimetric analysis. The reagent is sensitive and detective in the sense that they can be used to precipitate Pd in the stray acid medium: The reagent can be used for the estimation of Ni(II) in the presence of Pd(II) and Co(II) but not Cu(ll).